Meningkatkan Produksi Usaha Mikro Kecil Menengah (UMKM) Melalui Program Pelatihan Okara Dikelurahan Lewirato Kota Bima - Isti Mulyati; Nunung Faujiah; Nurlayli Istiqomah; Zyad Dilmi (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
MSMEs play an important role in national development, especially in absorbing labor,equalizing income, regional economic development, increasing non-oil and gas exports, and increasing gross domestic product (GDP). Challenges often faced by MSME economic actors include limited working capital, low human resource capacity, and low mastery of science and technology, resulting in generally uncertain business prospects.The development of training programs for Micro, Small and Medium Enterprises (MSMEs) is carried out systematically using consultation methods, production discussions and mentoring.